2016
DOI: 10.3947/ic.2016.48.4.309
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Mixed Respiratory Viral Infection in Children with Adenoviral Infection

Abstract: BackgroundAlthough adenovirus (ADV) infection occurs steadily all year round in Korea and the identification of respiratory viral coinfections has been increasing following the introduction of multiplex real-time polymerase chain reaction tests, the clinical impact of viral coinfection in children with ADV infection has rarely been reported.Materials and MethodsMedical records of children diagnosed with ADV infection were retrospectively reviewed. The enrolled children were divided into two groups based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…30,31 According to the previous study by Lee et al, multiple respiratory viral infections with HAdV were reported in 30.5% of children. 32 HRV was the most common co-infecting virus which occurring in 69.6% of multiple viral infections. 33 In addition, the most common combinations of multiple viral infections were HRV þ RSV and HRV þ HAdV and triple/quadruple viral infections accounted for a certain proportion similar to the results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 According to the previous study by Lee et al, multiple respiratory viral infections with HAdV were reported in 30.5% of children. 32 HRV was the most common co-infecting virus which occurring in 69.6% of multiple viral infections. 33 In addition, the most common combinations of multiple viral infections were HRV þ RSV and HRV þ HAdV and triple/quadruple viral infections accounted for a certain proportion similar to the results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, an increased risk of life-threatening disease (e.g., intensive care unit [ICU] admission, need for mechanical ventilation, or death) was identified in patients with ADV-RSV coinfections compared to RSV single-virus infections. In a secondary outcome analysis, FLU-RSV coinfections had an increase in LOS compared to RSV single-virus infections (274), while ADV coinfections were more likely to be associated with the need to treat with supplemental oxygen than were ADV single-virus infections (276). Furthermore, in cases of community-acquired pneumonia, viral-bacterial infection has been associated with a more complicated course (e.g., hospital death or mechanical ventilation for Ͼ7 days) than infections with bacteria alone, viruses alone, or no identified etiology (277).…”
Section: Molecular Panel Testing For Respiratory Viruses (I) Defininmentioning
confidence: 96%
“…Studies have shown that enhanced expression of E1A genes can activate the mitogen-activated protein kinase (MAPK) signalling pathway, allowing HAdv to proliferate continuously in respiratory epithelial cells (26). Persistent latent infection of the lung tissue by E1A genes may lead to airway remodelling (30).…”
Section: Discussionmentioning
confidence: 99%